EVALUASI PERHITUNGAN DAN PELAPORAN PAJAK PPH 22 ATAS PENEBUSAN BAHAN BAKAR MINYAK DI PT.PERTAMINA MANADO - Kussoy, Emerald Brilliant; Saerang, David Paul Elia; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Taxes are the main source of state revenue. Without taxes, the majority of state activities is difficult to be implemented. One of the biggest contributor to state revenue is taxes from the oil and gas industry. Fuel ( BBM ) is one type of fuel produced from refining crude oil . Crude oil from the earth refinery processed in advance to produce oil products, which including the fuel. Associated with the tax code, the fuel tax is the object of section 22 is subject to income tax levied by Pertamina and entities other than Pertamina engaged in the sale of fuel over petroleum products. The purpose of this study is to evaluate the tax calculation and reporting of the top 22 pph fuel redemption is in accordance with the PMK 154/03/2010. The analytical method used is descriptive analysis. The findings of this study is the calculation done by PT. Pertamina on the sale of products or the goods are delivered fuel oil, gas, and lubricants have done well or in accordance with the provisions of applicable tax of 0.30 % of the sales price in the gas station filling station Sindulang as Private, in income tax article 22 reporting PT. Pertamina already fully in accordance with the tax regulations ,reporting not later than 20 days after the tax period ends.